Analysis of Kapuk Waste at PT. Raja Indonesia Perkasa Suwayuwo Using the SWOT Method - Bahruddin; Pusakaningwati, Ayik (Journal Knowledge Industrial Engineering (JKIE), 2024)
This study aims to analyze the management of kapuk seed waste at PT. Raja Indonesia Perkasa Suwayuwo uses the SWOT (Strengths, Weaknesses, Opportunities, Threats) method. Kapuk seed waste, which is produced in significant quantities (5 tons/day), has not been optimally utilized despite containing economic potential such as oil (24-40%) and bioactive compounds. The research method involved qualitative and quantitative approaches, with data collected through observation, interviews, and questionnaires of 15 respondents. The SWOT analysis identifies internal (strengths and weaknesses) and external (opportunities and threats) factors, which are assessed using a Likert scale of 1-4. The results of the validity and reliability test showed a reliable research instrument (Cronbach's Alpha > 0.60). The SWOT cartesian chart places companies in Quadrant II, showing external opportunities such as government and technology support, but internal weaknesses such as reliance on manual machines and a lack of innovation. The recommended strategy is a turn around, which is to take advantage of external opportunities to address internal weaknesses, such as employee training and technology adoption.